Da improcedência à procedência liminar: hipóteses de incidência e aplicação da norma do art. 285-A do Código de Processo Civil de lege lata e de lege ferenda - Lima, Lucas Rister de Sousa (2014)
Over time and as society evolved, the civil procedural system has tended to conceive techniques intended to expedite judicial protection and case-law uniformity, in order to optimize the services provided by the Judiciary and make them more efficient. Article 285-A of the Brazilian Code of Civil Procedure embodies this trend, with features of both aspects and that, ultimately, in addition to abiding by the constitutional model in force, attempts to align it with and adapt it to new prevailing social standards (particularly in connection with dual jurisdiction) on behalf of procedural economy and rationality. This rule stands as a very important tool for better utilization of the civil procedural system in general, as a time-saving method for judges, clerks of justice and other practitioners of the law, avoiding the activities with little or no influence on the outcome of proceedings, thereby contributing to better adjudication results, with decreased expenditure of time and energy, as prescribed by the principle of timely judicial protection. Moreover, as it implies a substantial change in the how procedural acts unfold (beginning, in fact, at 'the end' of a proceeding s first phase), empirical application of the technique is somewhat hampered, which is not to say that it should cease to be applied or, or that its contribution to the improvement of the system as a whole should be denied, as this study attempts to demonstrate. The technique s power and potentialities in the face of an increasingly mass-oriented society with countless repetitive activities (and its clear reflections on the design of the Judiciary itself) allow concluding, without offense to the Constitution (especially the principle of due process and the adversarial principle) and in clear obedience of the principle of equality, in favor of extending the faculties of article 285-A of the Brazilian Code of Civil Procedure to the plaintiff as well, who would be granted the same privileges afforded to defendants under similar circumstances